MANAGEMEN FISIOTERAPI PADA KASUS XEROSIS EC MORBUS HANSEN MULTI BASILLER DI RS KUSTA KELET DONOROJO (STUDI KASUS) - Aldhita Inayah Firdausi; Isnaini Herawati; Teguh Prihastomo (Journal of Innovation Research and Knowledge, 2023)
Introduction: Xerosis is a term for dry skin that often occurs on the lower limbs, heels, elbows, and fingers. Xerosis is caused by reduced moisture due to loss of lipids and natural moisturizing factors in the Stratum Corneum. The purpose of this study is to determine the implementation of physiotherapy in reducing xerosis in both lower limbs and maintaining skin elasticity with. Methods: patients are given oiling treatment, ankle pumping, bridging exercise, balance exercise and sensory stimulus exercises on the feet for 4 weeks which are carried out 3x/week. Results: evaluation was carried out using Range Of Motion (ROM), Manual Muscle Testing, Anthropometry, ODSS (Overall Dry Skin Score). Conclusion: there is an increase in ROM, MMT, ODSS (Overall Dry Skin Score) and a decrease in Anthropometry after being given Exercise therapy for 4 weeks.